Walayah (Guardianship): The Authority Over A Woman's Choice in Marriage and How This Reflects A Desire To Control and Kafa'a (Equality): A Barrier To A Woman's Marriage Choice?. Issue 2 (2019) - Farooq, Muhammad
No abstract available